2014
DOI: 10.1136/jfprhc-2014-100878
|View full text |Cite
|
Sign up to set email alerts
|

Cost of unintended pregnancy in Norway: a role for long-acting reversible contraception

Abstract: ObjectivesThe objective of this study was to quantify the cost burden of unintended pregnancies (UPs) in Norway, and to estimate the proportion of costs due to imperfect contraceptive adherence. Potential cost savings that could arise from increased uptake of long-acting reversible contraception (LARC) were also investigated.MethodsAn economic model was constructed to estimate the total number of UPs and associated costs in women aged 15–24 years. Adherence-related UP was estimated using ‘perfect use’ and ‘typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…It is a single rod, containing 68mg of Etonogestrel to offer contraception for three years [1]. Contraceptive discontinuations contribute substantially to the total fertility rate, unwanted pregnancies,and induced abortions [2,3]. An estimated 13% of maternal mortality from unsafe abortion is due to unintended pregnancy [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is a single rod, containing 68mg of Etonogestrel to offer contraception for three years [1]. Contraceptive discontinuations contribute substantially to the total fertility rate, unwanted pregnancies,and induced abortions [2,3]. An estimated 13% of maternal mortality from unsafe abortion is due to unintended pregnancy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Neither motor nor attentional impulsivity was associated with pregnancy intentionality. This research suggests that nonplanning impulsivity may be a potential novel risk factor for unplanned pregnancy, an important finding given the adverse effects on maternal and infant health 4,5 and on health care costs 2,3 associated with unplanned pregnancies.…”
Section: Discussionmentioning
confidence: 79%
“…1 Unintended pregnancies are associated with high financial costs, 2,3 maternal depression and stress, and poorer infant health. 4,5 Unintended pregnancies typically result from failure to use contraception in women who are not purposefully trying to achieve pregnancy, inconsistent or incorrect use of effective contraceptives, or lack of contraceptive availability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Increasing IUC use may help to decrease the rates of adherence-related UP and the cost burden associated with these pregnancies. Studies in the USA 1 and Norway 8 have found that increasing LARC uptake may result in reduced rates of UP and hence a significant cost savings. To date, there is no study that has quantified the direct cost of UP in Canada or the proportion of this cost that can be attributed to imperfect contraceptive adherence.…”
Section: Introductionmentioning
confidence: 99%